Penggunaan Mobile Learning dengan Live Streaming Facebook pada Mata Pelajaran Qur’an Hadith - Zainiyati, Husniyatus Salamah; Muna, Nailul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aims to identify the use of Mobile Learning by using Facebook Live Streaming in the student learning process at MTs Robithotul Ashfiya' Sidokumpul Bungah Gresik for Qur'an Hadith subjects. This is motivated by the activities of the Qur'an Hadith teacher at MTs Robithotul Ashfiya, who are busy outside the madrasa, so most of the teaching and learning process uses bold methods. This study involved students in grades 7 (seven) in grading 9 (nine) and 1 (one) education staff at MTs Robithotul Ashfiya as Madrasah Operators. The research uses an exploratory case study method. The research approach uses qualitative methods to obtain accurate information about the effectiveness of using mobile learning with Facebook live streaming on Qur'an Hadith subjects at Madrasah Tsanawiyah Robithotul Ashfiya' Sidokumpul Bungah Gresik. The results of this study explain that the use of mobile learning with Facebook live streaming on Qur'an Hadith subjects at the Madrasah Tsanawiyah unit level runs effectively.